2012
DOI: 10.1530/joe-12-0420
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulation of Sirtuin 1 expression and implications to integrated responses in fasted mice

Abstract: Sirtuin 1 (SIRT1), a NAD C -dependent deacetylase, has been connected to beneficial effects elicited by calorie restriction. Physiological adaptation to starvation requires higher activity of SIRT1 and also the suppression of thyroid hormone (TH) action to achieve energy conservation. Here, we tested the hypothesis that those two events are correlated and that TH may be a regulator of SIRT1 expression. Forty-eight-hour fasting mice exhibited reduced serum TH and increased SIRT1 protein content in liver and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 67 publications
2
32
0
Order By: Relevance
“…Nuclear TRβ protein levels decrease in both of those organs with age, whereas nuclear TRα1 levels are unaltered. Notably, the same authors showed that total cellular TRβ protein levels increase during ageing in both liver and kidney (in the latter, TRα protein also increases), which might suggest that certain extra-nuclear non-genomic actions, several of which being reported to depend on TRs [13,14,22,24] are more pronounced during ageing. However, to our knowledge no information exists in the literature on this subject.…”
Section: Thyroid Gland Activity: Ageing Vs Healthy Ageingmentioning
confidence: 98%
See 3 more Smart Citations
“…Nuclear TRβ protein levels decrease in both of those organs with age, whereas nuclear TRα1 levels are unaltered. Notably, the same authors showed that total cellular TRβ protein levels increase during ageing in both liver and kidney (in the latter, TRα protein also increases), which might suggest that certain extra-nuclear non-genomic actions, several of which being reported to depend on TRs [13,14,22,24] are more pronounced during ageing. However, to our knowledge no information exists in the literature on this subject.…”
Section: Thyroid Gland Activity: Ageing Vs Healthy Ageingmentioning
confidence: 98%
“…A recent study addressed the effect of T3 on SIRT1 activity in vivo [22]. Transgenic mice harboring a dominant-negative mutation in TRβ, created to serve as a model of thyroid hormone resistance [119], have higher hepatic SIRT1 activity, and so do hypothyroid wild-type mice, compared to their respective wild-type littermates [22]. Conversely, in hypothyroid mice, T4 supplementation reduces liver SIRT activity [22].…”
Section: Healthy Ageing: Key Factors Involved and Their Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is supported by previous studies that SIRT1 protein levels, but not its mRNA, decrease by various stresses. 31,32 We have shown that activation of calpains causes impaired autophagy, mitochondrial dysfunction, and hepatocyte death after I/R. [4][5][6] As calpain inhibition suppressed both SIRT1 loss and cell death after I/R, calpains are, at least in part, an integral contributor to SIRT1 loss.…”
mentioning
confidence: 99%